Pyrrolidinones derived from (S)-pyroglutamic acid. Part 1. Conformationally constrained glutamate - Bailey, J; Cherry, D; Dyer, J; Moloney, M; Bamford, M; Keeling, S; Lamont, R (2000)
Novel conformationally constrained pyroglutaminols and pyroglutamates are readily available using an α,β-unsaturated bicyclic lactam as a template for diastereocontrolled enolate additions in the key step; zinc enolates are particularly effective in this regard. The bicyclic ring system both controls and permits the determination of ring stereochemistry. The utility of this methodology is demonstrated by a formal total synthesis of the NMDA receptor agonist, CPAA 11. © The Royal Society of Chemistry 2000.